Tryptanthrin Suppresses the Activation of the LPS-Treated BV2 Microglial Cell Line via Nrf2/HO-1 Antioxidant Signaling - Kwon, Young-Won; Cheon, So Yeong; Park, Sung Yun; Song, Juhyun; Lee, Ju-Hee (Frontiers in Cellular Neuroscience, 2017)
Microglia are the resident macrophages in the central nervous system (CNS) and play essential roles in neuronal homeostasis and neuroinflammatory pathologies. Recently, microglia have been shown to contribute decisively to neuropathologic processes after ischemic stroke. Furthermore, natural compounds have been reported to attenuate inflammation and pathologies associated with neuroinflammation. Tryptanthrin (indolo[2,1-b]quinazoline-6,12-dione) is a phytoalkaloid with known anti-inflammatory effects in cells. In present study, the authors confirmed middle cerebral artery occlusion (MCAO) injury triggers the activation of microglia in brain tissue, and investigated whether tryptanthrin influences the function of mouse murine BV2 microglia under LPS-induced inflammatory conditions in vitro. It was found tryptanthrin protected BV2 microglia cells against LPS-induced inflammation and inhibited the induction of M1 phenotype microglia under inflammatory conditions. In addition, tryptanthrin reduced the production of pro-inflammatory cytokines in BV2 microglia cells via nuclear factor erythroid 2-related factor 2 (Nrf2)/heme oxygenase 1 (HO-1) signaling and NF-κB signaling. The authors suggest that tryptanthrin might alleviate the progress of neuropathologies by controlling microglial functions under neuroinflammatory conditions.